Multivariate Prediction of Intraoperative Abandonment of Ileal Pouch Anal Anastomosis. Issue 5 (May 2020) - Poh, Keat S.; Qureshi, Sana; Hong, Young Ki; Moreno, Teresa; Stocchi, Luca; Hull, Tracy; Maron, David J.; Wexner, Steven D.; daSilva, Giovanna
Abstract : BACKGROUND: Restorative total proctocolectomy with IPAA may not be feasible in some patients because of technical intraoperative limitations. OBJECTIVE: This study aimed to assess preoperative predictors for intraoperative IPAA and review management. DESIGN: This is a retrospective review. SETTING: This study was conducted at Cleveland Clinic between January 2010 and May 2018. PATIENTS: Patients ≥18 years of age who underwent ileoanal pouch surgery were included. Patients with successful pouch creation as planned were grouped as "successful IPAA creation." Operative reports of patients who underwent alternative procedures were reviewed to identify cases when the pouch was preoperatively planned but intraoperatively abandoned (IPAA-abandoned group). Multivariate logistic regression models were developed to determine predictors of intraoperative pouch abandonment. We also reviewed the management of patients in whom the initial pouch creation failed. MAIN OUTCOME MEASURES: The primary outcomes measured were preoperative predictors for intraoperative ileoanal pouch abandonment. RESULTS: A total of 1438 patients were offered an ileoanal pouch; 21 (1.5%) experienced pouch abandonment due to inadequate reach (n = 17) and other technical reasons (n = 4). These patients underwent alternative procedures such as end or loop ileostomy with/without proctectomy. Multivariate logistic regression analysis indicated male sex (OR, 6.021; 95% CI, 1.540–23.534), BMI (OR, 1.217; 95% CI, 1.114–1.329), and a 2-stage procedure (OR, 14.510; 95% CI, 4.123–51.064) as independent factors associated with intraoperative abandonment of pouch creation. Alternative procedures were total proctocolectomy with end ileostomy (n = 14) and total abdominal colectomy with end ileostomy without proctectomy (n = 7). Ultimately, pouch creation was achieved in 6 of 21 patients after a median interval of 8.8 (range, 4.1–34.8) months. All patients had intentional weight loss before a reattempt and total abdominal colectomy with end ileostomy without proctectomy as their initial procedure. LIMITATIONS: This study was limited by its retrospective nature. CONCLUSIONS: Ileoanal pouch abandonment is rare and can be mitigated by initial total abdominal colectomy and weight loss. Male, obese patients are at a higher risk of failure. Intraoperative assessment of ileoanal pouch feasibility should occur before rectal dissection. See Video Abstract at http://links.lww.com/DCR/B156 . PREDICCIÓN MULTIVARIANTE DEL ABANDONO INTRAOPERATORIO DE LA ANASTOMOSIS ANAL CON BOLSA ILEAL: ANTECEDENTES: La proctocolectomía total restaurativa con anastomosis de bolsa ileoanal puede no ser posible en algunos pacientes debido a limitaciones técnicas intraoperatorias. OBJETIVO: Evaluar los predictores preoperatorios para el abandono intraoperatorio de la bolsa ileoanal y revisar el manejo. DISEÑO: Revisión retrospectiva. MARCO: Cleveland Clinic entre Enero de 2010 y mayo de 2018. PACIENTES: Pacientes > 18 años que se sometieron a cirugía de bolsa ileoanal. Los pacientes con una creación exitosa de la bolsa según lo planeado se agruparon como "creación exitosa de anastomosis de bolsa ileoanal". Se revisaron los informes operativos de los pacientes que se sometieron a procedimientos alternativos para identificar los casos en que la bolsa se planificó preoperatoriamente pero se abandonó intraoperatoriamente (grupo de "anastomosis anal de bolsa ileoanal abandonada"). Se desarrollaron modelos de regresión logística multivariante para determinar los predictores del abandono intraoperatorio de la bolsa. También revisamos el manejo de pacientes que fallaron en la creación inicial de la bolsa. MEDIDAS DE RESULTADOS PRINCIPALES: Predictores preoperatorios para el abandono intraoperatorio de la bolsa ileoanal. RESULTADOS: A un total de 1438 pacientes se les ofreció una bolsa ileoanal; 21 (1.5%) experimentaron abandono de la bolsa debido a un alcance inadecuado (n = 17) y otras razones técnicas (n = 4). Estos pacientes se sometieron a procedimientos alternativos como ileostomía final o de asa con / sin proctectomía. El análisis de regresión logística multivariante indicó género masculino (OR, 6.021; IC 95%, 1.540–23.534), índice de masa corporal (OR, 1.217; IC 95%, 1.114–1.329) y procedimiento en 2 etapas (OR, 14.510; IC 95%, 4.123–51.064) como factores independientes asociados con el abandono intraoperatorio de la creación de la bolsa. Los procedimientos alternativos fueron la proctocolectomía total con ileostomía final (n = 14) y la colectomía abdominal total con ileostomía final sin proctectomía (n = 7). Finalmente, la creación de la bolsa se logró en 6/21 pacientes después de un intervalo medio de 8.8 (rango, 4.1–34.8) meses. Todos los pacientes tuvieron pérdida de peso intencional antes de la reintenta y colectomía abdominal total con ileostomía final sin proctectomía como procedimiento inicial. LIMITACIONES: Naturaleza retrospectiva. CONCLUSIONES: El abandono de la bolsa ileoanal es raro y puede mitigarse mediante la colectomía abdominal total inicial y la pérdida de peso. Los pacientes masculinos y obesos tienen un mayor riesgo de fracaso. La evaluación intraoperatoria de la viabilidad de la bolsa ileoanal debe ocurrir antes de la disección rectal. Consulte Video Resumen en http://links.lww.com/DCR/B156 . (Traducción—Dr. Yesenia Rojas-Kahlil )